Disaster zone volcano in New York - Lee, Robert; Kahn, Harney; Watson, Sarah; Front Street Pictures production (La Crosse, Wis. : Distributed by Echo Bridge Home Entertainment, 2006)
A secret geothermal experiment has triggered a volcano underneath New York City, and now it's up to tunnel digger Matt Maclachlan, his team of workers, and his geologist ex-wife to save the city
Title from title screen
Director of photography, Adam Sliwinski ; editors, Trevor Mirosh, Bethany Handfield ; music, Michael Richard Plowman ; production designer, Michael Nemirsky
Cast: Costas Mandylor, Alexandra Paul, Michael Boisvert, Eric Breker, Ron Selmour, Pascale Hutton, Zak Santiago, Robert Moloney, Michael Ironside
DVD Format
Subtitle in Chine Traditional, Chinese Simplifies or English
Keywords: Volcanoes -- Drama; Disasters in motion pictures